Premenstrual Syndrome (PMS) pada Remaja Putri - Anisah Nur Asidah; Elok Dwi Cahyani; Aldhina Janurti; Aulia Rahma; Nadila Afriza; Miftahul Janna; Yeti Mareta Undaryati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Background: Premenstrual Syndrome (PMS) is a combination of physical, emotional, and behavioral symptoms that occur cyclically before menstruation and are commonly experienced by adolescent girls. Common symptoms include fatigue, abdominal pain, headaches, anxiety, and mood disturbances, which can affect sleep quality, concentration, and academic productivity. This article provides an in-depth examination of the definition, types, prevalence, causes, impacts, and management of PMS in adolescent girls. Based on epidemiological data, the prevalence of PMS is quite high, both globally and nationally, with incidence rates in Indonesia reaching 70–90% among women of reproductive age, and most cases beginning during adolescence. There are four main types of PMS: Type A (anxiety), Type H (hyperhidrosis), Type C (food cravings), and Type D (depression), each with specific characteristics and etiologies. Causes of PMS include hormonal imbalances of estrogen and progesterone, reduced serotonin levels, poor sleep quality, psychological stress, genetic factors, and unhealthy lifestyles. The impact of PMS on adolescents is complex, including decreased academic performance, social relationship disturbances, and reduced psychological well-being. Therefore, PMS management should be approached holistically through pharmacological (such as NSAIDs, antidepressants, and diuretics) and non-pharmacological (physical exercise, relaxation, lifestyle changes, and nutritional education) interventions. Environmental support and reproductive health education are crucial to help adolescents effectively manage PMS symptoms and improve their quality of life. This study is expected to serve as a foundation for promotive and preventive interventions in adolescent health care.